Анализ условий предельной степени демпфирования колебаний в электромеханической системе с упругими связями - Задорожний, Николай Алексеевич; Задорожняя, Инна Николаевна (НТУ "ХПИ", 2010)
On the basis of analysis of regularities of electromechanical interaction of the twomass systems is offered for achievement of high damping and minimum of swaying the electromechanical systems of main drives of rolling mills to apply generalized factors. The factors of electromechanical interaction take into account parameters of electric and mechanical subsystems, provide the optimum value of degree of stability of the complete electromechanical system.
Analysis of conditions of damping maximum degree of vibrations in the electromechanical system with resilient connections
Keywords: электропривод частотно-регулируемый; нагрузки динамические; колебания механические